Principal Decision Making: School Administrative Order - Herman; Luluk Zahrotul Hikmah; Muharrir; Marlinda (International Journal of Education, Language, and Social Science, 2025)
Effective and efficient school administration is highly desired by all parties, including stakeholders and education customers. However, in reality, school principals still use their authority in decision-making, so that the decisions made do not reflect joint decisions in school administrative order. The purpose of this study is to determine how school principals make decisions in school administrative order. This study uses a qualitative method with a literature review approach to examine and analyze previous studies relevant to the topic being researched, with the following steps: first, the researcher searches for or collects data sources and information; second, the researcher assessed the sources that had been found, third, the researcher analyzed the data and information to answer the research questions, and fourth, the researcher compiled a journal manuscript concept from all the results of the analysis of the data and information that had been collected. The results of the study show that, first, the principal's decision-making process is carried out through problem identification, analysis of the existing situation, development of alternatives, analysis of alternatives, and selection of the best alternative. Second, the factors that influence the principal in decision-making are position or status, problems that arise, situation, conditions, and objectives to be achieved in decision-making. Third, the styles used by principals in making decisions regarding school administrative order are the directive style, analytical style, conceptual style, and behavioral style. Fourth, the impact of decision making is greatly influenced by the principal's ability to make decisions appropriately and contextually in accordance with the stages of an effective decision-making process. Practical contributions can help improve the principal's capacity in decision-making by providing various information related to decision-making for school administrative order. Meanwhile, theoretical contributions can help develop better and more comprehensive decision-making theories in the effort to maintain school administrative order